Skreślenia - gry tekstowe Tadeusza Różewicza - Jaworski, Stanisław (Przestrzenie Teorii, 2007)
For nearly thirty years now Tadeusz Różewicz has published his poems with their earlier version (e.g. Płaskorzeźba Bas-relief), (1991). It can be described in terms of genetic criticism, talking of a way to the ultimate version, a way to self-cognition. It is also possible - and this is the task of this essay - to see in it a specific text game, aiming at double conveyance. A new whole is being created, which consists as if of the discarded, deleted elements, but here revoked in a new function - manifestation of the text in its many plots. From the clash of rough first drafts, deletions and "ultimate" versions as if a new poem arises, "the third poem", which exists only on the scene of reading.